Analysis of M42SP-7P on the Balinese Papyrus Script Printing Control System - Made Sudarma (Institute of Advanced Engineering and Science, 2016)
Script writing art in the lives of Balinese people has a very important function, particularly in terms of writing a sacred script such as writing an inscription on copper plate, bronze, silver, and gold, by using a penknife which required a persistence, patience, skill and experience by itself, since not all Balinese people is able to do this very complicated work. Considering the difficulty in writing a script on papyrus and the rarity of script writer experts, therefore the researcher gives appreciation on papyrus preservation and conservation. In the present time, sophisticated technology has replaced manual equipments which required a lot of manpower to be operated. Maybe also the inscription writing model with ancient language and writing has been done so many times with computer technology by using the printer as the interface for printing. In this research the Balinese script printing tools will be designed namely a penknife using robotic technology which mimicking human hand’s motion when writing a script on papyrus. Thought the script tool printer design through robotic technology in order to write a script on palm leaves is an important role of technology as an innovation strategy that is able to create new thinking, new ideas and inovation creative products. Eventually is also expected to satisfy the user as consumer and a new creative market.